2019
DOI: 10.1016/j.jtho.2019.05.036
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Postoperative Relapse in ALK-Positive Locally Advanced NSCLC Patient with Complete Pathological Response to Neoadjuvant Crizotinib

Abstract: with their long-term use. Moreover, corticosteroids may also increase the progression and spread of cancer. What is more, recent studies have emphasized that early use of steroids can damage their clinical benefit. Studies found that when corticosteroids were used at baseline (10 mg of prednisone equivalent) or in the early period of treatment (during the first 30 days), patients with NSCLC had significantly poorer overall survival. 4,5 Using alternatives to steroids (such as antihistamines) may also be an eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…However, the patient experienced rapid metastasis after discontinuation of short-term postoperative adjuvant crizotinib therapy. Zhong reported an ALK fusion mutation NSCLC patient who achieved pCR but developed rapid relapse due to discontinuation of crizotinib adjuvant therapy with negative ctDNA following 3.6 months of crizotinib adjuvant therapy ( 8 ). Altogether, these data indicated that neither complete pathological response nor negative ctDNA could be an effective predictor for discontinuation of short-term adjuvant targeted therapy in locally advanced NSCLC patients harboring MET ex14 mutation with complete surgical resection and also indicated the importance of long-term continuous postoperative crizotinib therapy even with negative ctDNA.…”
Section: Discussionmentioning
confidence: 99%
“…However, the patient experienced rapid metastasis after discontinuation of short-term postoperative adjuvant crizotinib therapy. Zhong reported an ALK fusion mutation NSCLC patient who achieved pCR but developed rapid relapse due to discontinuation of crizotinib adjuvant therapy with negative ctDNA following 3.6 months of crizotinib adjuvant therapy ( 8 ). Altogether, these data indicated that neither complete pathological response nor negative ctDNA could be an effective predictor for discontinuation of short-term adjuvant targeted therapy in locally advanced NSCLC patients harboring MET ex14 mutation with complete surgical resection and also indicated the importance of long-term continuous postoperative crizotinib therapy even with negative ctDNA.…”
Section: Discussionmentioning
confidence: 99%
“…4 However, postoperative relapse was seen with the emergence of an ALK mutation. 5 Acquired ALK mutations accounts for about one third of resistance to crizotinib, and several acquired resistance mutations have been identified including L1196M, G1269A, 1151Tins, L1152R, C1156Y, G1202R, and S1206Y mutations. 6 CNS relapse is another cause of treatment failure due to the poor penetration of crizotinib through the blood brain barrier.…”
Section: Discussionmentioning
confidence: 99%
“…There are several case reports on neoadjuvant crizotinib (60,61), and alectinib (62-65) as well, pointing to neoadjuvant ALK TKI approach as feasible, efficient and well tolerated.…”
Section: Selected Studies On Neoadjuvant Targeted Therapymentioning
confidence: 99%